Uji Toksisitas Akut Ekstrak Metanol Daun Keji Beling (Strobilanthes crispus BI.), Batang dan Bunga Jarak Tintir (Jatropha multifida L.) terhadap Larva Artemia salina Leach dengan Metode Brine Shrimp Lethality Test (BSLT) - Hamsidi, Rini; Wahyuni, Wahyuni; Sani, Asrul (Pharmauho: Jurnal Farmasi, Sains, dan Kesehatan, 2015)
Research on the acute toxicity test of methanol extracts of keji beling leaves (Strobilanthes crispus BI.), stems and flowers of jarak tintir (Jatropha multifida L.) against Artemia salina Leach larvae using Brine Shrimp Lethality Test method (BSLT) had been carried out. The purpose of this study was to determine the potency of acute toxicity of methanol extract which were shown by LC50 value. In this research, the sample methanol were obtained from a previous research. Acute toxicity tests was conducted to determine the LC50 values of plant extracts according to the method of Brine Shrimp Lethality Test. Results of the research showed methanol extract of keji beling leaves were not toxic with LC50 value 4427,95 Î¼g/mL, meanwhile stems and flowers of jarak tintir had low toxicity with LC50 225,09 and 253,26 Î¼g/mL, respectively. The value of LC50 influenced by the content of secondary metabolites in plants.Keywords : Acute toxicity test, Brine Shrimp Lethality Test, LC50, J. multifida, S. crispus